2018
DOI: 10.3389/fneur.2018.00846
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Osmolyte Pathways in Skeletal Muscle Inflammation: Novel Biomarkers for Myositis

Abstract: We recently identified osmolyte accumulators as novel biomarkers for chronic skeletal muscle inflammation and weakness, but their precise involvement in inflammatory myopathies remains elusive. In the current study, we demonstrate in vitro that, in myoblasts and myotubes exposed to pro-inflammatory cytokines or increased salt concentration, mRNA levels of the osmolyte carriers SLC5A3, SLC6A6, SLC6A12, and AKR1B1 enzyme can be upregulated. Induction of SLC6A12 and AKR1B1 was confirmed at the protein level using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…In DMD patients, upregulation of SMIT was observed at the protein level and colocalization studies showed that expression coincided with CD56+ fibers, a subset of CD206+ macrophages and T-cells, pointing towards involvement in the inflammatory and the successive regenerative response [ 6 ]. In vitro experiments have shown a significant upregulation of SLC5A3 mRNA in muscle cells exposed to pro-inflammatory cytokines [ 32 ]. Taken together, our results show increased protein levels of SMIT in mdx mice, especially in damaged muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…In DMD patients, upregulation of SMIT was observed at the protein level and colocalization studies showed that expression coincided with CD56+ fibers, a subset of CD206+ macrophages and T-cells, pointing towards involvement in the inflammatory and the successive regenerative response [ 6 ]. In vitro experiments have shown a significant upregulation of SLC5A3 mRNA in muscle cells exposed to pro-inflammatory cytokines [ 32 ]. Taken together, our results show increased protein levels of SMIT in mdx mice, especially in damaged muscle fibers.…”
Section: Discussionmentioning
confidence: 99%
“…We reported earlier that the osmolyte system becomes activated in myositis tissues [10] and in vitro in muscle cells exposed to pro-inflammatory cytokines [11]. In the present study we elaborate on the involvement of the MI transporter SLC5A3 in the degenerative and inflammatory changes associated with IBM.…”
Section: Introductionmentioning
confidence: 67%
“…Our study shows that SLC5A3 is upregulated in IBM muscle and that the osmolyte carrier localizes to the muscle fibers, blood vessels, and inflammatory cells. Overexpressed SLC5A3 has also been observed in other inflammatory myopathies and in muscular dystrophies [11]. Yet, the co-localization with the muscle fiber inclusions is peculiar for IBM, a muscle disease in which degenerative and inflammatory characteristics are equally prominent.…”
Section: Discussionmentioning
confidence: 99%
“…This study has several limitations that should be considered. Firstly, the effect of treatment on muscle inflammation was evaluated in CCL-136 cells exposed to cytokines [ 46 ]. In this study, the use of dystrophin-deficient muscle cells exposed to cytokines would have been a more suitable model.…”
Section: Discussionmentioning
confidence: 99%